Human Fcγ receptors compete for TGN1412 binding that determines the antibody's effector function. Issue 7 (29th April 2019) - Dudek, Simone; Weißmüller, Sabrina; Anzaghe, Martina; Miller, Lilija; Sterr, Sarah; Hoffmann, Katja; Hengel, Hartmut; Waibler, Zoe
Abstract: The first‐in‐human clinical trial of the CD28‐specific monoclonal antibody (mAb) TGN1412 resulted in a life‐threatening cytokine release syndrome. Although TGN1412 was designed as IgG4, known for weak Fc:Fcγ receptor (FcγR) interactions, these interactions contributed to TGN1412‐induced T‐cell activation. Using cell lines (TFs) expressing human FcγRI, ‐IIa, ‐IIb, or ‐III, we show that TGN1412 and TGN1412 as IgG1 and IgG2 are bound by FcγRs as it can be deduced from literature. However, upon coculture of TGN1412‐decorated T cells with TFs or human primary blood cells, we observed that binding capacities by FcγRs do not correlate with the strength of the mediated effector function. FcγRIIa and FcγRIIb, showing no or very minor binding to TGN1412, mediated strongest T cell proliferation, while high‐affinity FcγRI, exhibiting strong TGN1412 binding, mediated hardly any T‐cell proliferation. These findings are of biological relevance because we show that FcγRI binds TGN1412, thus prevents binding to FcγRIIa or FcγRIIb, and consequently disables T‐cell proliferation. In line with this, FcγRI − FcγRII + but not FcγRI + FcγRII + monocytes mediate TGN1412‐induced T‐cell proliferation. Collectively, by using TGN1412 as example, our results indicate that binding of monomeric IgG subclasses does not predict the FcγR‐mediated effector function, which has major implications for the design of therapeutic mAbs. Abstract : Using Fcγ receptor (FcγR)‐expressing cell lines and primary human immune cells indicated weak binding capacities of FcγRII but strong binding capacities of FcγRI for the superagonistic, CD28‐specific monoclonal antibody TGN1412. Of note, TGN1412‐induced, FcγR‐mediated T‐cell proliferation correlated inversely: FcγRII mediated strong while FcγRI mediated hardly any T‐cell proliferation.